Prostate Microbiota and Prostate Cancer: A New Trend in Treatment - Che, Bangwei; Zhang, Wenjun; Xu, Shenghan; Yin, Jingju; He, Jun; Huang, Tao; Li, Wei; Yu, Ying; Tang, Kaifa (Frontiers in Oncology, 2021)
Although the incidence and mortality of prostate cancer have gradually begun to decline in the past few years, it is still one of the leading causes of death from malignant tumors in the world. The occurrence and development of prostate cancer are affected by race, family history, microenvironment, and other factors. In recent decades, more and more studies have confirmed that prostate microflora in the tumor microenvironment may play an important role in the occurrence, development, and prognosis of prostate cancer. Microorganisms or their metabolites may affect the occurrence and metastasis of cancer cells or regulate anti-cancer immune surveillance. In addition, the use of tumor microenvironment bacteria in interventional targeting therapy of tumors also shows a unique advantage. In this review, we introduce the pathway of microbiota into prostate cancer, focusing on the mechanism of microorganisms in tumorigenesis and development, as well as the prospect and significance of microorganisms as tumor biomarkers and tumor prevention and treatment.